India : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
India rebounded strongly from its 1991 balance-of-payments crisis, aided by structural reforms and other policy adjustments. The government has sought to reinvigorate the process of structural and fiscal reform. The paper examines trends in interstate differences in rural poverty; reviews India's postal saving system and possible reform issues; describes and evaluates the current system of pensions and provident funds, and discusses reform options. The paper also briefly reviews the structure of and recent developments in the Indian foreign exchange market.